Volume 1: Aircraft Engine; Fans and Blowers; Marine; Honors and Awards 2017
DOI: 10.1115/gt2017-63331
|View full text |Cite
|
Sign up to set email alerts
|

The Design of a Large Diameter Axial Flow Fan for Air-Cooled Heat Exchanger Applications

Abstract: An axial flow fan design methodology is developed to design large diameter, low pressure rise, rotor-only fans for large air-cooled heat exchangers. The procedure aims to design highly efficient axial flow fans that perform well when subjected to off design conditions commonly encountered in air-cooled heat exchangers. The procedure makes use of several optimisation steps in order to achieve this. These steps include optimising the hub-tip ratio, vortex distribution, blading and aerofoil camber distributions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Fixed velocity and turbulence profiles at the fan outlet were used to specify the inlet boundary conditions. Circumferentially averaged outlet profiles for the M-fan at flow rates ranging from 260 to 380 m 3 /s were obtained from Wilkinson [41]. He measured these profiles from the hub to the tip of a periodic three-dimensional CFD model, approximately 0.1 m downstream of the fan blade trailing edge at the hub.…”
Section: Computational Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Fixed velocity and turbulence profiles at the fan outlet were used to specify the inlet boundary conditions. Circumferentially averaged outlet profiles for the M-fan at flow rates ranging from 260 to 380 m 3 /s were obtained from Wilkinson [41]. He measured these profiles from the hub to the tip of a periodic three-dimensional CFD model, approximately 0.1 m downstream of the fan blade trailing edge at the hub.…”
Section: Computational Setupmentioning
confidence: 99%
“…He measured these profiles from the hub to the tip of a periodic three-dimensional CFD model, approximately 0.1 m downstream of the fan blade trailing edge at the hub. Since Wilkinson [41] used the realisable k-ε turbulence model, the turbulence dissipation rate had to be converted to turbulence frequency using = /( * ), where * = 0.09 [42].…”
Section: Computational Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The air serves as the cooling fluid to condensate steam, flowing across a tube bundle (not shown). In this configuration a squared grid is present upstream the tubes and acts as pavement for operators (4). The fan design and operative parameters are summarized in Table 1.…”
Section: Cps Test Facility Descriptionmentioning
confidence: 99%
“…This dissertation focuses on the certification of fan performance, that follows ISO 5801 [3]. Given the size of the actual ACC fan, it is not possible to test it in its full-size, but scaling of the device is required to fit it to smaller facilities, like the Stellenbosh laboratory that was used in this case, where the maximum diameter is fixed at 1.5 m. This of course poses some problems when scaling performance (previous works [4] showed that the scaled performance fits quite well the full size pressure ratio, whilst underestimating efficiency). Another issue in this case is the derating of performance from ISO to real-life installation layout, that is a key issue like in most fan installations.…”
Section: Introductionmentioning
confidence: 99%